Representation formula for viscosity solution to a PDE problem involving Pucci's extremal operator. (February 2021) - Pozza, Marco
Abstract: We provide a representation formula for viscosity solutions to an elliptic Dirichlet problem involving Pucci's extremal operators. This is done through a dynamic programming principle derived from Denis et al. (2010). The formula can be seen as a nonlinear extension of the Feynman–Kac formula.